Mycofabrication of gold nanoparticles and evaluation of their antioxidant activities - Chakravarty I.; Pradeepam R.J.; Kundu K.; Singh P.K.; Kundu S. (My University, 2025)
Gold nanoparticles have found prominence in pharmaceutical applications due to their unique physical properties as well as their inert nature. Mycosynthesis of noble metal nanoparticles is less stringent and eco-friendly. In this paper, we have reported the economically-viable synthesis of gold nanoparticles, mediated by five different fungal strains Aspergillus flavus NCIM650, Phoma exigua NCIM1237, Aspergillus niger NCIM 616, Aspergillus niger NCIM 1025 and Trichoderma reesei NCIM 1186. An efficient approach for fungal growth was discussed wherein the biomass was cultivated in non-limiting conditions, followed by addition of gold salt solution. Cyclic Voltammetry studies were conducted to show the varying reducing capacities of these strains. The surface plasmon peaks for gold nanoparticles produced by Aspergillus flavus NCIM650, Phoma exigua NCIM1237, Aspergillus niger NCIM 616, Aspergillus niger NCIM 1025 and Trichoderma reesei NCIM 1186 were recorded as 536nm, 543nm, 542nm, 560nm, 537nm respectively. Based on the cyclic voltammetry studies and UV-Visible spectroscopy, transmission electron microscopy (TEM) analysis was done. Among the five strains, gold nanoparticles fabricated by Aspergillus niger NCIM 616 gave quite promising results. The antioxidant activities were evaluated using DPPH quenching assay and hydrogen peroxide assay. © 2015 Bentham Science Publishers.